Assessment of non-linearity in calorie–income relationship in Pakistan - Shabnam, Nadia (Frontiers in Nutrition, 2022)
This paper estimates the relationship between calorie consumption and income within a framework of nonparametric and semi-parametric methods, which allows for heterogeneity across households and possible nonlinearity in the relationship. The results, using a cross-sectional household survey data (2010-11) from Pakistan, indicate that calorie-income elasticity is sizeable and statistically significant across estimation techniques. The results also show that the elasticity is higher for the relatively poor households in the sample. The semi-parametric analysis also brings out little bit increase in calorie response to income changes at different income levels by including the explanatory variables in a tractable manner in the parametric part of regression techniques.